Impact of market and population pressure on production, incomes and natural resources in the dryland savannas of West Africa: bioeconomic modeling at the village level - Barbier, Bruno (International Food Policy Research Institute, 1996)
This paper introduces a modeling method which simulates a village's response to population and market pressure. The method combines a linear programming model with a biophysical model of soil condition and plant growth. The linear programming model simulates farmers' plans aggregated at the village level, and the biophysical model predicts yields and land degradation for different land use and cropping patterns. The method has been calibrated for two villages located in a semi-arid and a sub-humid savanna region in Burkina Faso in West Africa. Several simulations are carried out to the year 2030. Sensitivity tests are used to isolate the main factors of intensification, particularly to distinguish between the effects of ""population-pressure driven"" intensification from that of ""market driven"" intensification.